This preview shows page 1. Sign up to view the full content.
71. For
U
=
U
0
,Schr¨
odinger’s equation becomes
d
2
ψ
dx
2
+
8
π
2
m
h
2
[
E
−
U
0
]
ψ
=0
.
We substitute
ψ
=
ψ
0
e
ikx
. The second derivative is
d
2
ψ/dx
2
=
−
k
2
ψ
0
e
ikx
=
−
k
2
ψ
. The result is
−
k
2
ψ
+
8
π
2
m
h
2
[
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.
 Fall '08
 SPRUNGER
 Physics

Click to edit the document details